Effective Technology Integration: Closing the Digital Gap among High School Students - Cabasan, Ramonito Ariel (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the impact of technology integration strategies on digital inclusion among high school students, focusing on reducing disparities in access and digital literacy. Seventy-five out of 1,131 Grade 11 Senior High School students from a private school in Quezon City were surveyed to understand their demographic profiles, barriers to digital access, the effectiveness of digital literacy integration in the curriculum, the support for technology use in classroom activities, and the accessibility and inclusivity of digital resources. The research used a mixed-methods approach to assess digital access disparities and technology integration effectiveness. Quantitative data was used to analyze respondents' demographics and identify technology gaps, while qualitative insights explored contributing factors to digital disparity, ensuring comprehensive evidence and a deeper understanding of the intervention's impact and effectiveness. The findings highlight significant areas of concern, including internet connectivity, financial constraints, and access to digital devices, alongside a need for improved digital literacy, cybersecurity awareness, and teacher training. The results underscore the necessity for comprehensive support mechanisms to promote equitable and inclusive digital learning environments. To address these challenges, the study suggests implementing mechanisms such as financial support for acquiring necessary digital devices, improvements in internet infrastructure, and extensive training programs for teachers to enhance their digital literacy and teaching skills. By doing so, educational institutions can foster a more equitable and inclusive digital learning environment, ensuring that all students, regardless of their socioeconomic status, can access and benefit from technology-enhanced education. This holistic approach aims to bridge the digital divide and promote fairer educational opportunities through strategic technology integration.